2017
DOI: 10.1364/ome.7.001971
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rapid thermal annealing on the optical properties of GaAsSb alloys

Abstract: GaAsSb ternary alloys are fundamental components of advanced electronic and optoelectronic devices in the future. The presence of localized states could greatly affect the optical properties in GaAsSb alloy, which depend on the fluctuation of alloy composition. In order to optimize the optical properties, GaAsSb alloys were treated by rapid thermal annealing (RTA) at different temperatures, and the optical behaviors of the annealed samples were investigated in detail. During RTA, a significant reduction of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 40 publications
(59 reference statements)
0
7
0
Order By: Relevance
“…Figure 1(d) displays the PL spectra of the as-grown and RTA treated GaAsSb samples measured at 180 K. At this particular temperature, the peak position of the sample has redshifted to 49 meV after the RTA treatment. According to reference [27], the valence band can be modulated by incorporating Sb into GaAs, leading to a significant reduction in band gap [24]. It is noted that the PL emission of the asgrown GaAsSb sample almost disappears above 180 K. In contrast, the emission intensity of the RTA treated sample is much stronger.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1(d) displays the PL spectra of the as-grown and RTA treated GaAsSb samples measured at 180 K. At this particular temperature, the peak position of the sample has redshifted to 49 meV after the RTA treatment. According to reference [27], the valence band can be modulated by incorporating Sb into GaAs, leading to a significant reduction in band gap [24]. It is noted that the PL emission of the asgrown GaAsSb sample almost disappears above 180 K. In contrast, the emission intensity of the RTA treated sample is much stronger.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study [20], it was found that the localized degree displays a linear relationship with the Sb content. To eliminate the localized states, a rapid thermal annealing (RTA) process was used in later research [24]. It was found that a suitable annealing process could suppress defects or reduce localized states in GaAsSb alloys.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, there have only been a few reports on the optical properties of GaAsSb materials [43][44][45][46][47][48][49][50]. In addition, GaAsSb has been recognized as an important material for use in high-performance optoelectronic devices, and its optical properties are thus significant for the improvement of the performance of these devices.…”
Section: Gasb Alloy Emission Propertiesmentioning
confidence: 99%
“…It should be noted that the formation of localized states was related to Sb cluster formation inside the GaAs x Sb 1−x alloy, which was influenced by the rapid thermal annealing (RTA) temperature. Figure 9 shows the effects of the RTA temperature on the emission properties [50]. During the RTA process, a significant change in the PL, owing to the reduction of localized states, was observed.…”
Section: Gasb Alloy Emission Propertiesmentioning
confidence: 99%
“…[15][16][17] It is also beneficial to the improvement of performance of optoelectronic devices. In our previous research, localized states characteristics in GaAsSb/AlGaAs multiple QWs (MQWs) [18] and GaAsSb epitaxial layers [19,20] were reported. After rapid thermal annealing (RTA) treatment, the localized states in the GaAsSb alloy reduced effectively that indicates suppression of defects or localized states.…”
Section: Introductionmentioning
confidence: 99%